Observations on the Lunar and Tidal Influence on Gill Netting in the Bay of Bengal - PATI, S (Fishery Technology, 2017)
The effect of lunar and tidal influence on the landing of pelagic fish with drift gill nets has been studied for the first time from Bay of Bengal along the Oris a coast. The catchability of the gear was highest during the first quarter and lowest in the fourth quarter of the moon. The variation in catch rates during the four different quarters was not statistically significant. Contrary to the earlier belief, landing with gill net was not poor during the moonlit nights. The extensive use of bluish grey nylon twine matching with seawater in place of indigenous hemp or cotton twine, has largely eliminated the visibility of gear during the brighter. phase of the moon. The rate of exploitation was found to be significantly higher during the nights of neap tide, compared to those of spring tide. A plausible explanation for this phenomenon has been offered.